The relationships among functional traits of tardigrades (Tardigrada), their diet, and environmental conditions - Tůmová, Michala (Jihočeská univerzita, 2022)
In this thesis, I explore several ways how to use functional traits to study the tardigrade role in the soil food web. The goal of the thesis was to show that it is possible to study tardigrade ecology even without species identification. Trophic classification of tardigrades, as well as morphometric traits of each individual, were used as functional traits. First, I confirmed the existence of different trophic groups, testing the whole spectrum of potential diet in three tardigrade species from different trophic groups. I showed that tardigrades differed not only in the scope of ingested items but also in survival and fecundity under different types of diet. Secondly, I compared trophic group composition with species composition in natural tardigrade communities. The results showed that species, as well as trophic group composition, responded to the same environmental drivers. Trophic group composition enabled easier interpretation of the tardigrade role in the soil food web, while species composition illustrated also species-specific preferences that were not connected to their feeding habits such as preferences for different levels of soil moisture. Finally, I have used morphometric traits measured in each individual separately which allowed me for evaluation of inter-specific as well as intra-specific variation. As a result, buccal tube length was selected as a predictor of tardigrade feeding preferences among nematode, rotifer, and tardigrade prey. In summary, the thesis documented that functional traits provide a tool for the prediction of tardigrade feeding behaviour and detection of changes in the role of tardigrades along environmental gradients without the need of species identification.
The relationships among functional traits of tardigrades (Tardigrada), their diet, and environmental conditions
Keywords: želvušky; mikrofauna; Tardigrada; funkční vlastnosti; trofické skupiny; půdní potravní sítě; water bears; Tardigrada; functional traits; soil food web; trophic groups; microfauna